Beyond the self-reports: A review on objective pain measurement and its implications - Rasim ul Hasanat; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Current methods of pain measurement are inadequate in capturing the complexity of the pain experience. This limitation arises mainly because these methods tend to overlook the multiple dimensions of pain during assessment, heavily relying on self-reported measures, which inherently have their drawbacks. Self-reported measures aim to gauge the pain severity experienced by an individual, based solely on their perception of the most intense pain sensation. However, these measures are prone to various biases and may not accurately reflect the actual pain experienced. To overcome these limitations, a new system of pain assessment is necessary, which minimizes subjective involvement and provides a more accurate representation of pain. The ‘Pain Calculator’ is a newly developed tool that has demonstrated promising accuracy in measuring somatic pain in the low back region. This tool effectively overcomes the subjective biases characteristic of the self-reported measures and provides a reliable and clinically feasible alternative to the existing pain assessment tools. Keywords: Pain Measurement, Pain Assessment, Nociception Tests, Analogue Pain scale, Pain Severity, Pain Threshold